2007
DOI: 10.2106/jbjs.f.00313
|View full text |Cite
|
Sign up to set email alerts
|

Revision Total Hip Arthroplasty for Pelvic Discontinuity

Abstract: Therapeutic Level IV. See Instructions to Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 9 publications
7
68
3
8
Order By: Relevance
“…Dislocations are more common after difficult revision procedures like these because of component malposition, an absent or damaged abductor mechanism, or inadequate soft tissue tension [5,15,25]. In our study, only one of 24 patients experienced dislocation, which appears to be less than reported with other techniques [5,9,15,32,36]. We believe that our method's reasonably accurate restoration of the hip center and its control of the inclination and anteversion of the cage contributed to restoring the tension of the soft tissue and reducing impingement between the cage and femoral neck.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Dislocations are more common after difficult revision procedures like these because of component malposition, an absent or damaged abductor mechanism, or inadequate soft tissue tension [5,15,25]. In our study, only one of 24 patients experienced dislocation, which appears to be less than reported with other techniques [5,9,15,32,36]. We believe that our method's reasonably accurate restoration of the hip center and its control of the inclination and anteversion of the cage contributed to restoring the tension of the soft tissue and reducing impingement between the cage and femoral neck.…”
Section: Discussionmentioning
confidence: 43%
“…Once the appropriate position of the cage has been determined, our rapid-prototyping models indicate if the superior acetabulum provides sufficient contact and support for the cage; if not, a modified crest or 3-D printed augment can be added to the superior surface of the cage. Dislocation is a frequent problem with triflange cups, occurring in 16% to 26% of hips [5,9,32,36]. Dislocations are more common after difficult revision procedures like these because of component malposition, an absent or damaged abductor mechanism, or inadequate soft tissue tension [5,15,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DeBoer et al [5] previously reported 20 hips with pelvic discontinuity treated with a triflange component at a mean of 10 years and found bridging callous in 18 of 20 hips.…”
Section: Introductionmentioning
confidence: 98%
“…The implant manufacture generates individualized implants from the respective imaging (Fig. 4) 38 Taunton et al reported a revision rate of 30% (20/57) at 5.4 years and 21% dislocation rate most likely attributable to instability generated from pre-operative trochanteric escape performed in 51% of patients and possible traction injury to the superior gluteal nerve during exposure. 31 When comparing manufacture costs, triflange components are priced similar to other constructs used to treat pelvic discontinuity, including the ''cup-cage'' construct, a trabecular metal cup with an antiprotrusio cage (Zimmer, Inc, Warsaw, IN, USA).…”
Section: Custom Triflange Implantsmentioning
confidence: 99%